Jesus' entry into Jerusalem : in the context of Lukan theology and the politics of his day - Kinman, Brent. (Arbeiten zur Geschichte des antiken Judentums und des Urchristentums, 1995)
Taking into account the backgrounds of Graeco-Roman and Jewish 'triumphal entries', this volume deals with the Lukan version of Jesus' entry to Jerusalem and his subsequent 'cleaning' of its Temple. It is argued that Luke's account has been shaped by identifiable political and theological considerations, including the phenomenon of parousia and the place of Israel in the plan of God. Early chapters explore Luke's political milieu together with various entry phenomena from the ancient world, including the advent of governors, emperors and Jewish kings; a close examination of the Lukan text and context follow. This study breaks new ground in contributing to our understanding of how specific contemporary political issues and theological concerns led to the shaping of Luke 19:28-48 and context.